2019
DOI: 10.18203/2320-1770.ijrcog20192131
|View full text |Cite
|
Sign up to set email alerts
|

Weight gain and menstrual abnormalities between users of Depo-provera and Noristerat

Abstract: Background: Progesterone only injectable contraceptive provides long acting contraception against unwanted pregnancy. Alterations in menstrual pattern are a well known side effect of this effective contraceptive method. Objective of this study was to compare the weight gain and pattern of menstrual abnormalities in users of Depot Medroxyprogesterone Acetate (DMPA) and Norethisterone Enanthate (Noristerat) in LASUTH.Methods: Retrospective comparative study conducted over a 3year period (January 2013 to December… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…This is comparable to 15.35% and 15.7% reported fromPort-Harcourt and Uyo [15,16] but higher than 12.6% and 14.2% reported in Ife and Jos [17,18]. However the study prevalence was lower than 26%, 45.17%, 23.3% and 21.55% reported from other parts of the country such as Isagamu, Port Harcourt, Calabar and Lagos [6,[19][20][21]. These variations noted in various regions of Nigeria could be as a result of sociocultural and religious beliefs as well as clients perception of the type of contraceptive [20].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This is comparable to 15.35% and 15.7% reported fromPort-Harcourt and Uyo [15,16] but higher than 12.6% and 14.2% reported in Ife and Jos [17,18]. However the study prevalence was lower than 26%, 45.17%, 23.3% and 21.55% reported from other parts of the country such as Isagamu, Port Harcourt, Calabar and Lagos [6,[19][20][21]. These variations noted in various regions of Nigeria could be as a result of sociocultural and religious beliefs as well as clients perception of the type of contraceptive [20].…”
Section: Discussionsupporting
confidence: 58%
“…The weight gain may be due to improved appetite leading to increase in food intake. The injectables have also been found to cause slight water retention contributing to this weight gain [21].…”
Section: Fig 2 Continuation and Discontinuation Rates Of Poicsmentioning
confidence: 98%
“…Some mothers also chose to drop out when experiencing this problem. The results of the study also stated that most mothers experienced menstrual cycle disorders, namely amenorrhea 6,11 . Therefore researchers are interested in seeing how "The Infl uence of Old Use of Depo Medroxyprogesterone Acetate (DMPA) on Menstrual Cycle Disorders at RSIA Masyita Makassar".…”
Section: Introductionmentioning
confidence: 67%
“…With the mechanism evoked by the two hormones above against endometrial cells, this study showed that the use of DMPA which only contains progestin hormones can affect the endometrium and bleeding that occurs in the endometrium with the emergence of various complaints of menstrual disorders experienced by DMPA acceptors after more than 1 year of use. 15 The study entitled Weight gain and menstrual abnormalities between Depoprovera and Noristerat users 11 . This study used the following methods: A retrospective comparative study conducted over 3 years and involving 237 subjects who saw comparators using injectable hormonal contraceptives (DMPA or Noristerat).…”
Section: Discussionmentioning
confidence: 99%
“…The weight gain may be due to improved appetite leading to increase in food intake. The injectables have also been found to cause slight water retention contributing to this weight gain [19]. About 50-60% of implants users have been documented to report irregular vaginal bleeding patterns during the first year of use; however, it resolves spontaneously in subsequent years of use [20].…”
Section: Discussionmentioning
confidence: 99%